Microbial activities and transformations of substrates during composting, under controlled conditions, of straw plus corn steep liquor or poultry manure - Savoie, Jean Michel; Ricard, Isabelle; Olivier, Jean Marc (Mushroom Research, 2015)
Please see the full paper